2022
DOI: 10.3389/fnins.2022.974940
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency repetitive transcranial magnetic stimulation improves spatial episodic learning and memory performance by regulating brain plasticity in healthy rats

Abstract: BackgroundRepetitive transcranial magnetic stimulation (rTMS) is an effective way to stimulate changes in structural and functional plasticity, which is a part of learning and memory. However, to our knowledge, rTMS-induced specific activity and neural plasticity in different brain regions that affect cognition are not fully understood; nor are its mechanisms. Therefore, we aimed to investigate rTMS-induced cognition-related neural plasticity changes and their mechanisms in different brain regions.MethodsA tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…There is no clear recommendation for the use of cholinesterase inhibitors, NMDA receptor antagonists, or transcranial magnetic stimulation (TMS) in the treatment of PSCI. However, some studies have investigated the potential benefits of these treatments in PSCI patients ( Baskys and Hou, 2007 , Wu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is no clear recommendation for the use of cholinesterase inhibitors, NMDA receptor antagonists, or transcranial magnetic stimulation (TMS) in the treatment of PSCI. However, some studies have investigated the potential benefits of these treatments in PSCI patients ( Baskys and Hou, 2007 , Wu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Wu and colleagues recently reported that applying HF-rTMS over the prefrontal cortex (PFC) increases the expressions of the NMDAR in the PFC, hippocampus, and M1, which enhances the LTP-like synaptic plasticity and cognitive performance in healthy rats. 109 Moreover, they suggested that rTMS upregulated NMDAR levels through activating the BDNF/TrkB/Akt pathway. Notably, this study shows that rTMS-induced NMDAR-dependent LTP formation occurred both in the stimulus target and in the distant brain regions.…”
Section: How Rtms Modulates Neural Network In Brains Of Patients With Admentioning
confidence: 99%